Engineering Laboratory Experiments – a Typology. Issue 2 (4th May 2022) - Zwart, Sjoerd
Abstract : With the introduction of large commercial industrial laboratories at the end of the nineteenth century, many types of experiments were institutionalized that do not aim at testing hypotheses. This paper builds a typology of experiments in techno-science, by analysing more than two hundred and fifty real-life technical projects. This resulted in four testing types (tests of hypotheses, of designs, of means-end knowledge, and of models or software), three determining types (developing working principles, preferred actions, and determining values of variables or relationships between variables) and one trial-and-error type of pure exploration . The typology is developed by working back and forth between thick descriptions of the experiments including their goals, and the development of six criteria of differentiation, to wit: determining versus testing; measurement scales of (in)dependent variables; intrinsic versus instrumental value of the outcomes; proximate function of the outcome; distant role of the outcome in the embedded project; the descriptive or normative character of the proximate or distant outcomes. The typology opens up inspiring methodological and philosophical research questions.